Resistance of Coagulase-Positive Staphylococci to Methicillin and Oxacillin - Gravenkemper, Charles F. (1965)
Gravenkemper, Charles F. (University of Washington School of Medicine, Seattle), Jean L. Brodie, and William M. M. Kirby. Resistance of coagulase-positive staphylococci to methicillin and oxacillin. J. Bacteriol. 89:1005–1010. 1965.—Two strains resistant to methicillin were discovered among 541 strains of Staphylococcus aureus isolated in a clinical laboratory during a 1-yr period, and their properties were compared with those of strains isolated in Europe. The two strains were very active producers of penicillinase, and exhibited cross-resistance with other antistaphylococcal antibiotics. Like the European strains, our resistant cultures showed resistance to methicillin only with large inocula, and consisted of a mixture of cells. The great majority were sensitive and underwent early swelling and lysis, and only a small minority of the bacteria were able to grow in the presence of methicillin. The methicillin-resistant strains caused destruction of methicillin and oxacillin in vitro, but the rate of hydrolysis was slow. Antibiotic destruction was probably due to high concentrations of staphylococcal penicillinase, and not to another specific enzyme. These observations are helpful in explaining why resistance of staphylococci to the synthetic penicillins has not become a significant clinical problem.